UVB Radiation Protective Effect of Brown Alga Padina australis: A Potential Cosmeceutical Application of Malaysian Seaweed - Krishnapriya Thiyagarasaiyar; Camille Keisha Mahendra; Bey-Hing Goh; Lai Ti Gew; Yoon-Yen Yow (Cosmetics, 2021)
Marine natural products are a good source of antioxidants due to the presence of a wide range of bioactive compounds. Accumulating evidence proves the potential use of seaweed-derived ingredients in skincare products. This study aims to evaluate the ultraviolet (UV) protective activity of the ethanol and water extracts of Padina australis. As the preliminary attempt for this discovery, the total phenolic content (TPC) and total flavonoid content (TFC) were measured, followed by the in vitro antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing the power to shed light on its bioactivity. The UVB protective activity was examined on HaCaT human keratinocyte cells. The findings of this study reveal that the P. australis ethanol extract serves as a promising source of antioxidants, as it exhibits stronger antioxidant activities compared with the water extract in DPPH and the reducing power assays. The P. australis ethanol extract also demonstrated a higher level of total phenolic (76 mg GAE/g) and flavonoid contents (50 mg QE/g). Meanwhile, both the ethanol (400 µg/mL) and water extracts (400 µg/mL) protected the HaCaT cells from UVB-induced cell damage via promoting cell viability. Following that, LCMS analysis reveals that the P. australis ethanol extract consists of sugar alcohol, polysaccharide, carotenoid, terpenoid and fatty acid, whereas the water extract contains compounds from phenol, terpenoid, fatty acid, fatty alcohol and fatty acid amide. In summary, biometabolites derived from P. australis have diverse functional properties, and they could be applied to the developments of cosmeceutical and pharmaceutical products.